Ultra-spatial synchrotron radiation for imaging molecular chemical structure: Applications in plant and animal studies. Issue 4 (2007) - Yu Yu, Peiqiang Peiqiang
Abstract : Synchrotron-based Fourier transform infrared microspectroscopy (S-FTIR) has been developed as a rapid, direct, non-destructive, bioanalytical technique. This technique takes advantage of synchrotron light brightness and small effective source size and is capable of exploring the molecular chemical features and make-up within microstructures of a biological tissue without destruction of inherent structures at ultra-spatial resolutions within cellular dimension. To date there has been very little application of this advanced synchrotron technique to the study of plant and animal tissues' inherent structure at a cellular or subcellular level. In this article, a novel approach was introduced to show the potential of the newly developed, advanced synchrotron-based analytical technology, which can be used to reveal molecular structural-chemical features of various plant and animal tissues.